Synthesis of novel dihydrooxazine and oxazoline based sugar hybrids from sugar azides - Kurhade, Suresh E.; Ravula, Sudhir; Siddaiah, V.; Bhuniya, Debnath; Reddy, D. Srinivasa (Tetrahedron Letters, 2011)
A convenient one-step method for the synthesis of novel dihydrooxazine and oxazoline based sugar hybrids is reported starting from the readily accessible sugar azides and aldehydes. We have used Aube's protocol to achieve this transformation. The resulting glycoconjugates could be used to increase the diversity on the sugar backbone and may find applications as potential glycomimetics and in drug discovery. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Dihydrooxazine; Glycoconjugate; Hydroxy azide; Oxazoline; Sugar azide; Sugar hybrids